PERAN KBRI KUALA LUMPUR DALAM MENINGKATKAN PARIWISATA BANYUWANGI TAHUN 2018 – 2019 - Charista Harindha Bidari; Setyasih Harini; GPH Dipokusumo (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
Indonesia has considerable marine wealth with a long coastline. One of the potential coastal and marine resources in Banyuwangi. This study will discuss the potential of Banyuwangi tourism as international tourism and the role of representatives of the Indonesian government in Malaysia, namely the Indonesian Embassy in Kuala Lumpur to conduct diplomacy and bilateral cooperation to promote Banyuwangi tourism to Malaysia and gain national interest. Bilateral cooperation in the tourism sector is a very important part of the other cooperation, especially between Indonesia and Malaysia. The purpose of the cooperation is to strengthen, promote and develop bilateral cooperation between the two countries. This research will discuss with the perspective of international relations to analyze and evaluate how the steps are taken to promote the tourism potential of Banyuwangi and the tourism diplomacy steps taken to gain Indonesia's international interests. The tourism diplomacy efforts carried out by the Indonesian Embassy in Kuala Lumpur are not only carried out in collaboration with the government, but also through the business route (G to B) with Malaysian businesses and through the Malaysian community as well (G to B) to promote Banyuwangi tourism to tourists. Malaysia. Through diplomacy and bilateral cooperation carried out by the Indonesian Embassy in Kuala Lumpur as a state institution that interacts with Malaysian parties to promote Banyuwangi tourism, it is hoped that it can increase tourism in Banyuwangi. It is hoped that the increased tourism in Banyuwangi can support the Indonesian government in gaining Indonesia's national interests. Keywords : Banyuwangi tourism, tourism diplomacy, bilateral cooperation.